Strategi Pembelajaran Kooperatif dalam Menumbuhkan Sikap Toleransi Beragama - Jainal Abidin; Wahyu Widodo (Malewa: Journal of Multidisciplinary Educational Research, 2025)
Indonesia’s rich diversity of races, religions, ethnicities, languages, and cultural backgrounds necessitates the cultivation of moderate and tolerant attitudes to maintain social harmony. Despite this diversity, various cases of intolerance continue to occur, often triggering tension, conflict, and even violence among individuals or groups. These conditions highlight the crucial role of education, particularly Islamic Religious Education (PAI), in fostering tolerance within the school environment. This study aims to describe the learning strategies employed by the PAI teacher and to analyze their effectiveness in developing religious tolerance among students of Class X TITL 1 at SMKN 1 Bendo. This research adopts a qualitative approach, utilizing interviews, observations, and documentation for data collection. The data were analyzed through data reduction, data display, and verification. The findings reveal that the PAI teacher consistently applied cooperative learning strategies throughout the 2023/2024 academic year. The implementation of this strategy proved effective in fostering students’ religious tolerance, as reflected in the positive interactions among them. Non-Muslim students reported feeling accepted, respected, and comfortable among their predominantly Muslim classmates. These findings indicate that cooperative learning can serve as a relevant and effective pedagogical approach to strengthening tolerance in classrooms characterized by diversity.